(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: The study was conducted to determine the proportion and species composition of oral fungi by morphology and molecular biology. Methods: The study was designed using the experimental descriptive research method in the laboratory, including fungal culture on Sabouraud Dextrose Agar, serological testing, fungal culture and classification on CHROMagar™ Candida agar, species identification by PCR – RFLP with primer genes ITS-1, ITS -4 using restriction enzyme MSP-1 and gene sequencing. Results: Among 55 strains isolated, morphological identification showed that C. albicans accounted for the highest proportion of 65.5% (36/55), followed by C. tropicalis (12.7%), and unknown species up to 10.9% (6/55). Gene sequencing showed 10 fungal species identified, of which: C. albicans accounted for the highest proportion of 60% (33/55); C. tropicalis 20% (11/55); followed by other less common species such as C. dubliniensis, C. glabrata, C. krusei, C. parapsilosis, C. metapsilosis, Meyerozyma caribbica taking 1.8% (1/55) for each; and C. mesorugosa sharing 3.6% (2/55). Through gene sequencing, some rare pathogenic species such as Kodamaea ohmeri 3.6% (2/55) and Meyerozyma caribbica 1.8% (1/55) were detected. Conclusions: C. albicans accounted for the highest proportion through both morphological identification and molecular biology identification (65.5% and 60% respectively). Some rare species such as Kodamaea ohmeri 3.6% (2/55) and Meyerozyma caribbica 1.8% (1/55) were detected.